Characteristics of Exogenous Allergen in Breast Milk and Their Impact on Oral Tolerance Induction - Kosmeri, Chrysoula; Rallis, Dimitrios; Kostara, Maria; Giapros, Vasileios; Siomou, Ekaterini; Tsabouri, Sophia (Frontiers in Pediatrics, 2022)
Food allergy is a common health problem in childhood since the prevalence is estimated to range from 6.5-24.6% in European countries. Recently, a lot of research has focused on the impact of breastfeeding on oral tolerance induction. Since it was found that breast milk contains immunologically active food antigens, it would be very helpful to clarify the factors of antigen shedding that promotes oral tolerance. This narrative review aimed to summarize the latest evidence from experimental and human studies regarding allergen characteristics in human milk that may influence oral tolerance induction. A literature search in PubMed, Medline, and Google Scholar was conducted. The diet of the mother was found to have a direct impact on allergen amount in the breastmilk, while antigens had different kinetics in human milk between women and depending on the antigen. The mode of antigen consumption, such as the cooking of an antigen may also affect the allergenicity of the antigen in human milk. The dose of the antigen in human milk is in the range of ng/ml, however, it is found to have a tolerogenic effect. Furthermore, the presence of antigen-specific immunoglobulins, forming immune complexes with antigens, found more tolerogenic compared to free allergens in experimental studies, and this is related to the immune status of the mother. While examining available data, this review highlights gaps in knowledge regarding allergen characteristics that may influence oral tolerance.